MANAJEMEN TEKNIS AKREDITASI INSTITUSI UNGGUL BAGI PERGURUAN TINGGI KEAGAMAAN ISLAM NEGERI (PTKIN) - Islami, Nisa (Jurnal Tawadhu, 2018)
Problems college religious Islamic state (ptkin) to the beginning of 2018 looks just three college accredited A. About the birth assumption ptkin have the quality of the management of the lower than the PTU. Whereas the quality of ptkin has been shown in the National even international good aspects of the quality of faculty, students or the other. Similarly, with the budget allocation between ptkin with PTU still experiencing inequality. so reasonable if PTU little has the advantage of quality management compared to ptkin. Technical management is meant to how PTKIN technically plans, form a team, evaluates, prepares documents and documents, reviews, scores, and runs the accreditation visitation process in a neat, orderly manner so as to deliver PTKIN to get A (superior)accreditation.Kata Kunci: Akreditasi Institusi Perguruan Tinggi, Manajemen teknis, Mutu Perguruan Tinggi, PTKIN.